Pyrochlore Material Yb_2Ti_2O_7: A Model Quantum Spin Ice - Perimeter Institute (Perimeter Institute, 2012)
We discuss the thermodynamic properties of the model
exchange quantum spin ice material Yb_2Ti_2O_7. Using exchange parameters
recently determined from high-field neutron scattering measurements, we
calculate the thermodynamic properties of this model system. We find very good
agreement with the heat capacity, entropy and magnetization measurements on the
materials. We show that, in the weak quantum regime, quantum fluctuations lead
to the selection, within the spin-ice manifold, of a conventional ordered
ground state. However, the excitations above the ground state and their
dynamics remain highly non-trivial. They consist of weakly bound
spinon-antispinon pairs separated by long strings.
We present several pieces of indirect evidence that the
low temperature phase transition observed in these materials is to this
conventional ordered state.
Keywords: Condensed Matter